Answer:
Step-by-step explanation:
Answer:
1) y=(-1/4)x+(11/4)
2) y=(4)x-33
3) y=(2/3)x-11/3
4) y=(5)x-2
5) y=(3)x-7
6) y=(-1/4)x+(6)
Step-by-step explanation:
1) y=mx+b 3=(-1/4)(-1)+b b= 11/4
2) y=mx+b -5=(4)(7)+b b= -33
3) y=mx+b -5=(2/3)(-2)+b b= -11/3
4) y=mx+b 3=(5)(1)+b b= -2
5) y=mx+b -1=(-3)(-2)+b b= -7
6) y=mx+b 7=(1/4)(4)+b b= 6
Answer:
Option (2)
Step-by-step explanation:
Given expression is ÷
We further simplify this expression,
÷
=
=
=
Therefore, will be the quotient of the given expression.
and for which the given expression is not defined.
Option (2) will be the answer.
x3[x+4y=1]
-
3x+5y=10
-1y=-9
x-1 [-1y=-9]
y=9
Here, 4³√(3x-3)² + 2 = 38
= 4³ (3x - 3) = 38 - 2
= 192x - 192 = 36
= 192x = 192 + 36
= x = 228/192
= x = 1.1875 [ Final Answer ]
Hope this helps!